1987
DOI: 10.1111/j.1749-6632.1987.tb48769.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Tetrachloro‐p‐Hydroquinone and Other Metabolites of Hexachlorobenzene on Hepatic Uroporphyrinogen Decarboxylase Activity with Reference to the Role of Glutathionea

Abstract: Exposure of rats to HCB caused a dose-dependent depletion of GSH. Chlorophenolic and sulfur-containing metabolites of HCB incubated with GSH-free rat liver cytosolic protein drastically diminished the UROD activity. In addition, HCB also exhibited inhibitory potency. The most effective compounds studied were TCH and its oxidation product, chloranil. Incubation of liver cytosolic protein and of GSH with HCB and its metabolites yielded results that suggested interaction between the compounds and cell constituent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Hepatic GSH content in rats was found to be decreased by 50% within 24 h following oral administration of HCB (200 mg/kg) (Ingebrigtsen et al, 1981). A dose-dependent depletion of GSH in HCB exposed rats was found in another study (Koss et al, 1987). Our results were in agreement with these works.…”
Section: Gsh and Gsh-related Enzymes In Brainsupporting
confidence: 91%
“…Hepatic GSH content in rats was found to be decreased by 50% within 24 h following oral administration of HCB (200 mg/kg) (Ingebrigtsen et al, 1981). A dose-dependent depletion of GSH in HCB exposed rats was found in another study (Koss et al, 1987). Our results were in agreement with these works.…”
Section: Gsh and Gsh-related Enzymes In Brainsupporting
confidence: 91%
“…It is feasible that reactive oxygen species such as peroxides and free radicals (cf Ferioli et al 1984) are increasingly formed and that with advancing age of the animals their detoxication declines. The consequence could be glutathione depletion followed by a functional impairment of the uroporphyrinogen decarboxylase activity (Koss et al 1987). Further investigations into the reasons for the observed exceptional delayed onset of porphyria in the PCB 180 pretreated animals are therefore indispensable.…”
Section: Discussionmentioning
confidence: 99%
“…The above finding represents an unusual pathway for alkoxyl/ketoxy radical and/or HNE production not involving redox-active metals and may explain, at least in part, the potential carcinogenicity of not only PCP but also other widely used halogenated aromatic carcinogens (hexachlorobenzene, Agent Orange, and brominated flame-retardants) since these chemicals can be metabolized in vivo , or oxidized to tetra-, di-, or mono-XQ. Our findings showed that XQ may interact with ROOH and cause deleterious effects via facilitated generation of alkoxyl/ketoxy radicals and/or HNE and hence elevated damage to macromolecules.…”
Section: Conclusion and Future Researchmentioning
confidence: 88%